A Module Test of CCDA： an Array to Select the Centrality of Collisions in Heavy Ion Collisions - 付芬 林炜平 刘星泉 黄美容 WADARoy 张苏雅拉吐 石福栋 韩瑞 靳增雪 刘建立 任培培 赵明辉 陈志强 王建松 (Chinese physics letters, 2014)
A test result of a module for the collision centrality detector array （CCDA）, a simple detector array for the event classification of the centrality, is presented. The CsI（Tl） module has PMTs on both ends to read out signals. The beam test results indicate that it provides a good light charged particles （LCP） identification and a reasonable energy resolution. The energy spectra of LCPs are compared with the GEANT simulation.